The relative importance of social responsibility in determining organizational effectiveness: Student responses - Kraft, Kenneth L. (Journal of business ethics, 1991)
This paper investigates the relative importance of social responsibility criteria in determining organizational effectiveness. The organizational effectiveness menu was used as a questionnaire with a sample of 151 senior undergraduates. Each respondent was asked to rate the importance of the criteria from three constituent perspectives within a service organization: (1) as a manager, (2) as an investor, (3) as an employee. Later, a subsample of students (n=61) responded to the same questionnaire acting as a manager in an assigned case study. The results indicated that students acting as managers, investors, or employees rate social responsibility criteria among the least important of the determinants of organizational effectiveness. Moreover, while specific situations may call for changes in the relative importance of these criteria, social responsibility criteria were not viewed, generally, as the most important determinants of organizational effectiveness.